2013
DOI: 10.1017/s0007485312000661
|View full text |Cite
|
Sign up to set email alerts
|

Wheat bulb fly (Delia coarctata, Fallén, Diptera: Anthomyiidae) larval response to hydroxamic acid constituents of host-plant root exudates

Abstract: Wheat bulb fly (WBF, Delia coarctata, Fallén, Diptera: Anthomyiidae) is a pest of commercial importance in wheat, barley and rye, with attacked crops failing to produce full potential yields. Females do not oviposit in association with a host-plant; therefore, prompt location of a suitable host is critical to the survival of the newly hatched larvae. The objective of this study was to conduct choice test bioassays to assess the attraction of WBF larvae to specific chemical constituents of WBF host-plant root e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Another specialized root herbivore, the wheat bulb fly ( Delia coarctata ), showed remarkable attraction to wheat seedling exudates (Rogers and Evans 2013). MBOA attracted larvae in a dose-dependent fashion and might contribute to the activity of the exudate, while DIMBOA elicited a weaker response.…”
Section: Biological Effects Of Bxdsmentioning
confidence: 99%
“…Another specialized root herbivore, the wheat bulb fly ( Delia coarctata ), showed remarkable attraction to wheat seedling exudates (Rogers and Evans 2013). MBOA attracted larvae in a dose-dependent fashion and might contribute to the activity of the exudate, while DIMBOA elicited a weaker response.…”
Section: Biological Effects Of Bxdsmentioning
confidence: 99%
“…The larvae of the wheat bulb fly use chemotaxis and chemokinesis to locate host plants and are known to use primary and secondary metabolites, including carbon dioxide, hydroxamic acids, syringic acid and vanillic acid, as search cues. It has been suggested that primary metabolites such as carbon dioxide act as search triggers for wheat bulb fly larvae to induce searching behaviour which makes the larvae more likely to encounter the more plant specific secondary metabolites when they are near a suitable host plant (Rogers & Evans, 2013, 2014; Rogers et al , 2013). Further studies are needed to assess whether exudates from attractive versus non‐attractive lines of the Watkins collection have different behavioural effects on wheat bulb fly larvae and if there are any differences in root exudate chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Wheat bulb fly eggs were harvested from potato fields in East Lothian, UK (56°02′32.5050″N, 2°46′45.3388″W). The eggs were washed in 0.3% NaOCl solution for 2 min and rinsed in sterile distilled water for sterilization (Bellows & Fisher, ; Rogers & Evans, ). Eggs were then housed in sterile 90‐mm‐diameter Petri dishes containing vermiculite (moistened with sterile distilled water) on black nylon mesh and stored at 5 °C for 2 months (Rogers, ).…”
Section: Methodsmentioning
confidence: 99%
“…Arenas were the same as those used by Marriott & Evans () and Rogers & Evans (). In brief, they consisted of a black filter paper (Whatman 551; 90 mm diameter) placed in the centre of a glass Petri dish (140 mm diameter).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation